Implementation of Change Management by the Principal at the Driving School at State Senior High School 1 Segedong - Subagio, Agus (Riwayat: Educational Journal of History and Humanities, 2025)
"Senior High School 1 Segedong faces challenges in managing change to improve the quality of education, particularly in dealing with resistance to new policies and limited resources. This study aims to analyze how the school principal implements change management in the Sekolah Penggerak (Driving School) Program at the school. A qualitative approach with a case study method was used to gather data through interviews, observations, and documentation. The results of the study indicate that effective communication is key to overcoming barriers to change, followed by enhancing the skills of educators and providing adequate motivation. Additionally, continuous evaluation supports the successful implementation of change, although resistance from some parties still exists. The positive impact of this change management is reflected in the transformation of the school culture, improved teacher performance, and better student learning outcomes. In conclusion, effective change management can create a more dynamic and adaptive educational environment at Senior High School 1 Segedong."